Deceased donor skin allograft banking: Response and utilization - Gore Madhuri; De Anuradha (Indian Journal of Plastic Surgery)
Background: In the absence of xenograft and biosynthetic skin substitutes, deceased donor skin allografts is a feasible option for saving life of patient with extensive burn injury in our country. Aims: The first deceased donor skin allograft bank in India became functional at Lokmanya Tilak Municipal (LTM) medical college and hospital on 24 th April 2000. The response of Indian society to this new concept of skin donation after death and the pattern of utilization of banked allografts from 2000 to 2010 has been presented in this study. Settings and Design: This allograft skin bank was established by the department of surgery. The departments of surgery and microbiology share the responsibility of smooth functioning of the bank. Materials and Methods: The response in terms of number of donations and the profile of donors was analyzed from records. Pattern and outcome of allograft utilization was studied from specially designed forms. Results: During these ten years, 262 deceased donor skin allograft donations were received. The response showed significant improvement after counselling was extended to the community. Majority of the donors were above 70 years of age and procurement was done at home for most. Skin allografts from 249 donors were used for 165 patients in ten years. The outcome was encouraging with seven deaths in 151 recipients with burn injuries. Conclusions: Our experience shows that the Indian society is ready to accept the concept of skin donation after death. Use of skin allografts is life saving for large burns. We need to prepare guidelines for the establishment of more skin banks in the country.